The value of life in English law: revered but not sacred?. (2nd January 2018) - Heywood, Rob; Mullock, Alexandra
Abstract : Terms such as sanctity and inviolability have failed to provide a legally coherent or ethically sound principle upon which to determine the scope of the intrinsic value of life against extrinsic, quality-of-life considerations in a medical context. In their recent work, Margaret Brazier and Suzanne Ost introduce a new term, reverence for life, which they suggest may be more appropriate when attempting to navigate the murky waters of the meaning of life and the value that should be attached to it. They suggest that reverence should be utilised as an alternative that better reflects the nuances and the realities of the dilemma. This paper explores the existing difficulties before considering how the principle of reverence might provide a principled compromise over when the presumption in favour of preserving life should be rebutted.